2015
DOI: 10.1016/j.actamat.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation mechanisms in a zirconium alloy in the high-temperature regime: An in situ TEM investigation

Abstract: Dislocation mechanisms responsible for the high-temperature mechanical properties of a Zr alloy have been investigated using in situ straining experiments between 250°C and 450°C. At 250°C and 300°C, the results show a steady and homogeneous dislocation motion in prismatic planes, with little cross-slip in the pyramidal and/or basal planes. At 350°C, the kinetics of mobile dislocations becomes very jerky and inhomogeneous, in agreement with a dynamic strain aging mechanism. Above this temperature, the motion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…The disappearance of the jogs at high temperature has also been reported elsewhere (Ecob and Donaldson, 1985). Moreover, the jogged-screw theory is challenged by a recent in-situ TEM study (Caillard et al, 2015) done at similar temperature (250 o C-450 o C) as Morrow et al (2013), where the climb of jogs is not observed.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…The disappearance of the jogs at high temperature has also been reported elsewhere (Ecob and Donaldson, 1985). Moreover, the jogged-screw theory is challenged by a recent in-situ TEM study (Caillard et al, 2015) done at similar temperature (250 o C-450 o C) as Morrow et al (2013), where the climb of jogs is not observed.…”
Section: Introductionmentioning
confidence: 71%
“…It has been demonstrated that it increases almost linearly with the dislocation velocity, then reaches a maximum value after a short transient process, and starts to decrease afterward. The stresses acting on a moving dislocation include the applied resolved shear stress, lattice friction, solute dragging stress ( dislocations move at low velocity (of order 10 nm/s according to Caillard, 2015), which leads to a higher travel time mentioned in Eq. 7 and thus lower creep rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations